Basophils are dispensable for the establishment of protective adaptive immunity against primary and challenge infection with the intestinal helminth parasite Strongyloides ratti. - Martina Reitz; Marie-Luise Brunn; David Voehringer; Minka Breloer (Public Library of Science (PLoS), 2018)
Infections with helminth parasites are controlled by a concerted action of innate and adaptive effector cells in the frame of a type 2 immune response. Basophils are innate effector cells that may also contribute to the initiation and amplification of adaptive immune responses. Here, we use constitutively basophil-deficient Mcpt8-Cre mice to analyze the impact of basophils during initiation and execution of the protective type 2 responses to both, a primary infection and a challenge infection of immune mice with the helminth parasite Strongyloides ratti. Basophil numbers expanded during parasite infection in blood and mesenteric lymph nodes. Basophil deficiency significantly elevated intestinal parasite numbers and fecal release of eggs and larvae during a primary infection. However, basophils were neither required for the initiation of a S. ratti-specific cellular and humoral type 2 immune response nor for the efficient protection against a challenge infection. Production of Th2 cytokines, IgG1 and IgE as well as mast cell activation were not reduced in basophil-deficient Mcpt8-Cre mice compared to basophil-competent Mcpt8-WT littermates. In addition, a challenge infection of immune basophil-deficient and WT mice resulted in a comparable reduction of tissue migrating larvae, parasites in the intestine and fecal release of eggs and L1 compared to mice infected for the first time. We have shown previously that S. ratti infection induced expansion of Foxp3+ regulatory T cells that interfered with efficient parasite expulsion. Here we show that depletion of regulatory T cells reduced intestinal parasite burden also in absence of basophils. Thus basophils were not targeted specifically by S. ratti-mediated immune evasive mechanisms. Our collective data rather suggests that basophils are non-redundant innate effector cells during murine Strongyloides infections that contribute to the early control of intestinal parasite burden.